Triple Γ-Homomorphisms and Bi - Γ -Derivations on Jordan Γ-algebra - Shaheen, Rajaa C.; Taher, Hasan R. (Iraqi Journal of Science, 2023)
In this paper, we introduce the concept of Jordan –algebra, special Jordan –algebra and triple –homomorphisms. We also introduce Bi - –derivations and Annihilator of Jordan algebra. Finally, we study the triple –homomorphisms and Bi - –derivations on Jordan algebra.